The protein tyrosine phosphatase 1B inhibitor MSI-1436 stimulates regeneration of heart and multiple other tissues - Ashley M. Smith (Nature Portfolio, 2017)
The enzyme inhibitor that regenerates multiple tissues A naturally occurring small molecule shows promise as a drug for tissue and organ repair and regeneration. Viravuth Yin of the Kathryn W. Davis Center for Regenerative Biology and Medicine with colleagues in the US found that treating zebrafish with an intraperitoneal injection of MSI-1436, which inhibits the enzyme ‘protein tyrosine phosphatase 1B’, increased the rate of regeneration of an amputated caudal fin and of partially removed heart muscle without apparent tissue malformation. Intraperitoneal injection of MSI-1436 in adult mice also reduced the size of an induced heart infarction, improved survivability, triggered new heart muscle formation and stimulated regeneration after skeletal muscle injury. Effective doses for tissue regeneration in both animals were much lower than the maximum tolerated doses found for humans in clinical trials for potential treatment of obesity and diabetes.